1994
DOI: 10.1111/j.1464-410x.1994.tb07483.x
|View full text |Cite
|
Sign up to set email alerts
|

Same day diagnostic service for new cases of haematuria – a District General Hospital experience

Abstract: The same day diagnostic service has not been difficult to administer. Patient acceptability was excellent and design objectives were achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…One-stop services are well established practise for haematuria, [8][9][10] as well as in other specialties, [11][12][13] and have been suggested by some authors as ap ossibility for testicular pathology, 4,14 but have not been accepted in this setting as yet. With little evidence that '2-week wait' initiatives impact on survival, 15,16 and growing pressure to find alternative mechanisms of improving services in general, onestop approaches are al ogical progression.…”
Section: Discussionmentioning
confidence: 99%
“…One-stop services are well established practise for haematuria, [8][9][10] as well as in other specialties, [11][12][13] and have been suggested by some authors as ap ossibility for testicular pathology, 4,14 but have not been accepted in this setting as yet. With little evidence that '2-week wait' initiatives impact on survival, 15,16 and growing pressure to find alternative mechanisms of improving services in general, onestop approaches are al ogical progression.…”
Section: Discussionmentioning
confidence: 99%
“…The OSMC aims to see all patients within 30 d of referral, as the importance of investigating haematuria with minimal delay is well established (Hasan et al , ; Ho et al , ; Wallace et al , ). Audit revealed that this was achieved 81% of the time for the first 100 patients, with the range of waiting times between 6 and 50 d. Of the 19 people (19%) who waited longer than 30 d to be seen at OSMC, 7 individuals (7%) experienced delay because they declined or missed the original appointment due to personal commitments or ill health.…”
Section: Waiting Timementioning
confidence: 99%
“…A same-day diagnostic service for new cases of haematuria has successfully been introduced at some hospitals in the UK, resulting in a shorter hospital-based delay and an increase in the number of diagnostic cystoscopies performed within 4 weeks (12).…”
mentioning
confidence: 99%